RME-based e-worksheets with Liveworksheet: A tool to enhance mathematical conjecturing abilities in statistics learning - Supriani, Yani; Giyanti, Giyanti (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This research is motivated by the low ability of students to make mathematical conjectures in statistics learning, especially on the topic of measures of central tendency, which is caused by the lack of interactivity and student involvement in mathematics learning. To overcome this, the study aims to develop and analyze the effectiveness of Electronic Student Worksheets (E-LKPD) based on Realistic Mathematics Education (RME) with Liveworksheet as an interactive learning medium. This study uses a research and development method (R&D) with a quasi-experimental design. The subjects of the study were seventh-grade junior high school students who participated in statistics learning. Data were collected through a mathematical conjecture ability test, observation of student engagement, and a questionnaire of student responses to the learning medium. The results showed that E-LKPD based on RME with Liveworksheet significantly improved students’ mathematical conjecture abilities, as evidenced by the increase in average scores before and after the use of the media. In addition, students showed high enthusiasm and active involvement during the learning process. In conclusion, the use of E-LKPD based on RME with Liveworksheet is effective as a tool to improve mathematical conjecture abilities in statistics learning, while increasing student motivation and participation.